The Importance Of Family Education To Instill Children’s Moral Character In The Era Of Industrial Revolution 4.0 - Litasari, Vena Nur; Pramukti, Ratna Handayani; Farikhah, Nur Alfi; Hidayah, Ratna (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Family education is a means of forming the most basic moral character of children. However, in the present era of gadget addiction in children is increased due to lack of attention and parental supervision as well as the failure of the elderly in his distortions. Causing the child to not control a good life pattern. The purpose of this study. To provide an expansion of knowledge and understanding for parents to be able to apply family education. The negative impact on the child one of them makes the child less sensitive to the homework, and addicted to playing gadgets because of the time they are utilizing by playing games. So it is necessary to expand the knowledge and understanding of family education in the hopes that parents can perform their role well through effective parenting patterns to form the values of good children's moral character